Vertical stratification and its impact on device performance in a polycarbazole based copolymer solar cells. Issue 16 (18th March 2015) - Wang, Tao; Scarratt, Nicholas W.; Yi, Hunan; Coleman, Iain F.; Zhang, Yiwei; Grant, Richard T.; Yao, Jizhong; Skoda, Maximilian W. A.; Dunbar, Alan D. F.; Jones, Richard A. L.; Iraqi, Ahmed; Lidzey, David G.
Abstract : Vertical stratification in PCDTBT1:PC71 BM bulk heterojunction solar cells were investigated by neutron reflectivity and found to have profound impacts on device performance. Abstract : Using neutron-reflectivity, we study vertical stratification and device performance in bulk hetero-junction organic photovoltaic (OPV) cells consisting of a blend of PC71 BM with a carbazole-based donor–acceptor copolymer PCDTBT1. We find that when the blend is cast on a PEDOT:PSS/ITO anode, a PC71 BM-depleted (polymer-rich) layer is formed at the PEDOT:PSS interface, whilst a PC71 BM-depleted layer is instead located at the air-interface when the same blend is cast on a solution processed MoO x thin film. OPV device characterization measurements indicate that unfavourable vertical segregation can have a profound effect on OPV device characteristics via increased charge recombination.